PENERAPAN KOOPERATIF NUMBERED HEADS TOGETHER DALAM MENINGKATKAN HASIL BELAJAR ILMU PENGETAHUAN ALAM MATERI GAYA - nugroho, wahyu setyo; Wapa, Andi (Consilium: Education and Counseling Journal, 2024)
The aim of this study was to improve learning objectives for students in the Natural Sciences force material for fourth-grade students at elemntary school through the implementation of the Numbered Head Together Cooperative learning model. This study utilized a classroom action research design and was executed over two cycles, with each cycle comprising four stages: a. Planning, b. Implementation, c. Observation, d. Reflection. The participants of the study included 25 fourth-grade students. The research employed observation and test sheets as its testing instruments, utilizing these methods to gather data. The findings indicated that in Cycle I, 9 out of 25 students achieved the KKM, resulting in 36% classical completeness. Conversely, in Cycle II, the number of students reaching the KKM rose to 21 out of 25, leading to an 84% classical completeness. The results demonstrated a significant improvement in learning objectives for students when employing the Numbered Heads Together Cooperative learning model in the Science of Force Material which corresponded with the Cycle I classical completeness of 36% and the increased Cycle II classical completeness of 84%.